Genetic overlap between personality and life satisfaction - Bratko, Denis; Butković, Ana; Vukasović, Tena (2011)
Life satisfaction or ―cognitive judgment of different aspects of person‘s life‖ is related to personality. The purpose of this study was to explore genetic and environmental influences on both personality and life satisfaction, and genetic and environmental overlap between life satisfaction and personality. Data was collected via mail from 339 twin pairs (36 MZM, 49 DZM, 69 MZF, 71 DZF, 114 DZO), aged between 15 and 22 (M=18.6, SD=2.31). All participants completed NEO-FFI and Pavot and Diener‘s Satisfaction with Life Scale. For personality the best fitting model was an AE model with heritablities in the 43-60% range. For life satisfaction the best fitting model was an AEs model with heritability of 83%. Bivariate analyses showed that there is genetic overlap between life satisfaction and all five personality factors and environmental overlap with neuroticism, extraversion and conscientiousness.
Knjiga sažetaka nije tiskana, već je dostupna isključivo na službenoj internetskoj stranici: http://www.ecp2011.org/assets/Uploads/program/FINAL_PROGRAMME/KEYNOTESOASYMPOSIUMROUNDTABLE.pdf
Projekt MZOS
ENG